Povezanost tekmovalne uspešnosti biatloncev med starostnima kategorijama mlajših članov in članov - Pančur, Neva (Šport (Ljubljana), 2021)
The aim of the study was to analyze the correlation in competition performance between junior and senior age categories of both genders in biathlon. For the period studied, the aim was to determine which country is the most successful in the number of medals won (for both genders combined) in the largest competitions in the junior and senior age categories. The baseline sample included 797 competitors of which 410 were men and 387 women from 31 countries. The study analyzed the period of 24 racing seasons, from 1996/97 to 2019/20. Participants in the junior category achieved a much higher proportion of placements in the top 10 in selected competitions than participants in the senior category. Additionally, a significant dropout of athletes when they moved to the senior category was observed. There were no statistically significant differences between the genders according to the groups formed within the Junior category (p = 0.429) or within the Senior category (p = 0.833). In our sample for both genders (males: p = 0.478; females: p = 0.343), no statistically significant correlations in terms of competitive performance between the analyzed competitive categories were observed.
Keywords: biathlon; biatlon; competition performance; člani; juniors; mlajši člani; seniors; sport; šport; tekmovalna uspešnost